Engineering Functionalized 2D Metal-Organic Frameworks Nanosheets with Fast Li+ Conduction for Advanced Solid Li Batteries - Xu, Laiqiang (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.